KEBIJAKAN DIVIDEN DAN VOLATILITAS HARGA SAHAM: PERIODE SEBELUM DAN SELAMA PANDEMI COVID-19 - Chintia Angelina; Rizky Eriandani; Felizia Arni Rudiawarni (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
Abstract Stock price volatility is a risk that must be faced by shareholders when owning a share. High volatility indicates that a company’s stock price is move very quickly and the difference between the highest and the lowest price is very significant. Stock price volatility can be influenced by several factors, one of the factor is dividend policy which consists of dividend payout ratio and dividend yield. Dividends carry information that show company’s performance so dividend can cause a reaction in the market in which can affect the company’s stock price. This study aims to analyze whether dividend payout ratio and dividend yield can affect stock price volatility. This study was carried out for all company that listed on the IDX during 2017-2021. The data used in this study is secondary data and using purposive sampling to determine the sample that will be used. The number of samples used in this study was 1867 and the analysis technique used wast multiple linear regression test. The results of this study indicate that dividend payout ratio and dividend yield have a significant effect and han an opposite relationship. This study shows that the higher dividend payout and dividend yield, the stock price volatility will be lower. In addition, the results of this study also show that firm size and earning per share also have a significant effect on stock price volatility. Future research can focus on other factors that can affect stock price volatility dividend policy and use other external factors that can affect stock price volatility.